Meeting in the middle: TVET programs' education-employment linkage in developing contexts - Katherine Caves; Andrea Ghisletta; Ursula Renold; Johanna Kemper (ETH Zurich, KOF Swiss Economic Institute, 2019)
Technical and vocational education and training (TVET) programs are most successful at supporting youth labor markets when they combine education and employment. Education-employment linkage theory describes this combination in terms of power-sharing between actors from the education system and their counterparts in the employment system over key processes in the curriculum value chain of curriculum design, curriculum application (program delivery), and curriculum updating. The KOF Education-Employment Linkage Index measures linkage at every function in a TVET program where actors from the two systems interact, aggregating those into processes and phases and eventually an index score. We apply that index to the largest upper-secondary TVET programs in Benin, Chile, Costa Rica, and Nepal. We find that Benin has relatively high education-employment linkage, while the other three countries score very low. Benin's situation is unique because its TVET program is moving from employer-led to linked, rather than the typical employer integration into an education-based program. Other countries with large informal economies, low formal education and training rates, and existing non-formal employer-led training may be able to implement similar approaches using functionally equivalent institutions. Furthermore, we summarize the results of discussions with policy-maker focus groups in the four case study countries.
Keywords: 330; vocational education and training; VET; TVET; education-employment linkage; KOF EELI; development economics